Colette [videorecording (DVD)] - Westmoreland, Wash; Knightley, Keira, 1985-; West, Dominic, 1969-; Gough, Denise (Universal Pictures Home Entertainment, 2018)
After marrying 'Willy', a successful Parisian writer, Colette is transplanted to the intellectual and artistic splendor of Paris. Willy convinces Colette to ghostwrite a semi-autobiographical novel about a witty and brazen country girl named Claudine, sparking a bestseller and a cultural sensation, inspiring additional Claudine novels. Colette's fight over creative ownership and gender roles drives her to overcome societal constraints, revolutionizing literature, fashion and sexual expression.